Role of the host cell in bacteriophage T4 development. I. Characterization of host mutants that block T4 head assembly. - Revel, H R (1980)
To study the role of the host cell in bacteriophage T4 infection, we selected more than 600 mutant host-defective bacteria that absorbed and were killed by phage T4+ but were unable to support its growth. The mutants were grouped into seven classes by the growth patterns of T4 phages carrying compensating mutations (go mutants [grows on]), selected on four prototype host-defective strains. Lysis and DNA synthesis experiments indicated that classes A, AD, D, and B (the majority of the host-defective mutants) block T4+ development at an assembly step, class C mutants affect an early stage in phage development, and class F mutants appear to act at more than one stage. Analysis of T4+ infection in the assembly-defective mutants by in vitro complementation, electron microscopy, and sodium dodecyl sulfate-polyacrylamide gel electrophoresis showed that the host-defective mutations interfere with T4+ capsid formation at the level of phage gene 31 function, before assembly of any recognizable capsid structure. The mutations map near purA, but at two or possibly three different sites. The go mutant phages able to overcome the host defect carry mutations in either gene 31, as found by others for similar defective hosts, or in the gene for the major capsid protein (gene 23). The gene 23 go mutations do not bypass the requirement for gene 31 function. These results suggest that at least three components must interact to initiate T4 head assembly: gp31, gp23, and one or more host factors. The compensatory effects of mutational alterations in these components are highly allele specific, consistent with the view that phage and host components interact directly in protein complexes.